Oral delivery of antioxidant enzymes for effective treatment of inflammatory disease. (April 2021) - Zeng, Zhiying; He, Xiao; Li, Changying; Lin, Shan; Chen, Hui; Liu, Libing; Feng, Xuli
Abstract: Oral administration of protein is very challenging for therapeutic applications due to its instability and easy degradation in the gastrointestinal tract. Herein, we reported an approach to encapsulate native anti-inflammatory proteins in wind chimes like cyclodextrin (WCC) for efficient oral protein delivery. The amphiphilic WCC can self-assemble into nanoparticles in aqueous solution and achieve superior encapsulation of two antioxidant enzymes such as superoxide dismutase (SOD) and catalase (CAT) by simply mixing with protein solution, avoiding any extra cumbersome steps that might inactivate protein. WCC nanovehicles can effectively protect enzyme activity and enhance their intracellular delivery. SOD and CAT co-loaded WCC nanoparticles (SC/WCC) can integrate the synergistic effect of SOD and CAT for enhancing the removal of reactive oxygen species (ROS), effectively inhibit the inflammatory response by reducing the secretion of proinflammatory factors and protect cells from ROS-induced oxidative damage. In the mouse colitis model, SC/WCC administered orally was able to efficiently accumulate in the inflamed colon, significantly inhibited the expression of proinflammatory mediators and notably alleviated the symptoms related to colitis. Therefore, we believe that the strategies we described here may provide a convenient and powerful platform for the treatment of other inflammatory diseases. Graphical abstract: Image 1 Highlights: Amphiphilic wind chime-like cyclodextrin (WCC) for effective oral enzyme delivery has been prepared. Superoxide dismutase and catalase co-loaded WCC nanoparticles (SC/WCC) had a good protective effect on their enzyme activity. SC/WCC nanoparticles can enhance the ROS scavenging ability of SOD and CAT to protect cells from oxidative damage. SC/WCC nanoparticles administered orally can significantly reduce the symptoms of DSS induced colitis.